2005
DOI: 10.7205/milmed.170.8.663
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Abnormal Eating Behaviors Associated with Cyclical Readiness Testing in a Naval Hospital Active Duty Population

Abstract: Studies of abnormal eating behaviors in active duty military personal have found rates similar to or higher than the general population. We have reviewed these studies and extended the research to examine abnormal eating behaviors in a heterogeneous population at a major military medical center. We found high rates of body dissatisfaction, abnormal eating behaviors, and worry about passing the semiannual personal fitness assessment in both men and women. Abnormal eating behaviors were associated with worrying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 0 publications
1
43
0
1
Order By: Relevance
“…Not only are they susceptible to various types of trauma exposure (including MST and combat), male and female service members are also subjected to regimented lifestyles and strict regulations, including physical fitness and weight requirements. 9 It is also possible that individuals who are more vulnerable to developing an ED, endorsing symptoms such as overexercise and placing a high emphasis on weight and shape, may be drawn to the military due to its emphasis on physicality and strict physical training. 63 Several studies found that enlisted service members in the youngest age group who were White, non-Hispanic, and members of the Marine Corps have elevated rates of EDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only are they susceptible to various types of trauma exposure (including MST and combat), male and female service members are also subjected to regimented lifestyles and strict regulations, including physical fitness and weight requirements. 9 It is also possible that individuals who are more vulnerable to developing an ED, endorsing symptoms such as overexercise and placing a high emphasis on weight and shape, may be drawn to the military due to its emphasis on physicality and strict physical training. 63 Several studies found that enlisted service members in the youngest age group who were White, non-Hispanic, and members of the Marine Corps have elevated rates of EDs.…”
Section: Discussionmentioning
confidence: 99%
“…16,18,19 In addition to high rates of trauma and psychological conditions comorbid with EDs, there are specific features of military life that potentially can increase the risk for the development of an ED among military service members and veterans, including: strict physical fitness requirements; weighins and weight regulations; deployment; the possibility of being exposed to or witnessing violence; death, dying, and harm to oneself or others during combat; killing during combat; and changes in eating behavior while in the service. 9,14,20,21 Military sexual trauma (MST) is another possible facet of military life that may have serious consequences for those who experience it. Research shows that MST is associated with poorer emotional and psychological functioning, 22,23 including the development of PTSD and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Given the robust link between disordered eating and obesity (Hudson, Hiripi, Pope, & Kessler, 2007), disordered eating may promote overweight/obesity in military personnel. The military's rigorous physical readiness standards and occupational consequences for exceeding weight standards also appear to foster a culturally ingrained awareness of eating and weight (Carlton, Manos, & Van Slyke, 2005;Warner et al, 2007). Therefore, examining factors associated with eating and weight problems in this potentially vulnerable population is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Often our patients are overweight and under enormous pressures to maintain normal weight for active duty status. Carlton et al 22 found that active duty men used diet pills at a year-round rate of 3.5% but the rate increased to 14.9% around the times for weigh-ins and measurements. The weight standards, although important for military bearing and readi-ness, place our service members at higher risk for eating disorders, unhealthy diets, and use of supplements for weight loss.…”
Section: Discussionmentioning
confidence: 99%